2014
DOI: 10.1115/1.4027488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Purely Viscous Non-Newtonian Flow in an Abdominal Aortic Aneurysm

Abstract: It is well known that blood has non-Newtonian properties, but it is generally accepted that blood behaves as a Newtonian fluid at shear rates above 100 s-1. However, in transient conditions, there are times and locations where the shear rate is well below 100 s-1, and it is reasonable to infer that non-Newtonian effects could become important. In this study, purely viscous non-Newtonian (generalized Newtonian) properties of blood are incorporated into the simulation-based framework for cardiovascular surgery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 48 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…This can potentially affect our results in two different ways. First, the WSS vector field obtained from a Newtonian and nonNewtonian assumption can be different, although these differences have been shown to be small in patient-specific AAAs [38]. Second, variations in viscosity affect the near-wall fluid velocity in Eq.…”
Section: P 10mentioning
confidence: 99%
“…This can potentially affect our results in two different ways. First, the WSS vector field obtained from a Newtonian and nonNewtonian assumption can be different, although these differences have been shown to be small in patient-specific AAAs [38]. Second, variations in viscosity affect the near-wall fluid velocity in Eq.…”
Section: P 10mentioning
confidence: 99%
“…Rigid wall and Newtonian blood rheology were assumed. It has been shown that the Newtonian assumption produces reasonable WSS patterns in AAAs (Marrero et al 2014) and that vessel deformation leads to relatively minor changes in overall flow topology (Duvernois et al 2013). Figure 1 shows one of the two AAA models, to exemplify the anatomy of the model, morphology of volumetric flow waveform, and the nature of mesh.…”
Section: Methodsmentioning
confidence: 99%
“…carotid, the blood is exposed to high shear rates and so could be considered as a Newtonian fluid (Zamir, 2005;Kim, 2009;Nichols et al, 2011). It is believed that blood could be considered as a Newtonian fluid at shear rates above 100 s-1 (Marrero et al, 2014). On the other hand, in small arteries and tissues other models should be considered.…”
Section: Pulsating Blood Flowmentioning
confidence: 99%